2014
DOI: 10.18632/oncotarget.1802
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor splice variants activating the full-length receptor in mediating resistance to androgen-directed therapy

Abstract: Upregulation of constitutively-active androgen receptor splice variants (AR-Vs) has been implicated in AR-driven tumor progression in castration-resistant prostate cancer. To date, functional studies of AR-Vs have been focused mainly on their ability to regulate gene expression independent of the full-length AR (AR-FL). Here, we showed that AR-V7 and ARv567es, two major AR-Vs, both facilitated AR-FL nuclear localization in the absence of androgen and mitigated the ability of the antiandrogen enzalutamide to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
231
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(249 citation statements)
references
References 38 publications
11
231
1
1
Order By: Relevance
“…A key question in the field has been whether AR-Vs regulate a classical AR-driven transcriptional program or whether they have distinct gene targets, with evidence for both concepts being reported (Guo et al 2009, Hu et al 2009, Chan et al 2012, Tsai et al 2012, Cao et al 2014. Recently, work from Dehm's group has provided a possible explanation for these discrepant findings by identifying proliferative vs anti-proliferative AR gene signatures mediated by differences in DHT dose or AR expression, with the former mitotic gene signature resembling that driven by AR-Vs (Li et al 2013).…”
Section: Ar Splice Variantsmentioning
confidence: 99%
See 1 more Smart Citation
“…A key question in the field has been whether AR-Vs regulate a classical AR-driven transcriptional program or whether they have distinct gene targets, with evidence for both concepts being reported (Guo et al 2009, Hu et al 2009, Chan et al 2012, Tsai et al 2012, Cao et al 2014. Recently, work from Dehm's group has provided a possible explanation for these discrepant findings by identifying proliferative vs anti-proliferative AR gene signatures mediated by differences in DHT dose or AR expression, with the former mitotic gene signature resembling that driven by AR-Vs (Li et al 2013).…”
Section: Ar Splice Variantsmentioning
confidence: 99%
“…The finding that AR-Vs can heterodimerize with AR-FL or with other AR-Vs , Cao et al 2014, Xu et al 2015 raises the possibility that the nature and relative expression of different AR-Vs and AR-FL in single cells could influence distinct transcriptional outputs.…”
Section: Ar Splice Variantsmentioning
confidence: 99%
“…Other investigators have suggested that targeting both AR-V7 and the AR ligand-binding domain may be useful in early therapies. 10,11 AR-V7 appears to be induced after ADT, potentially selecting for circulating tumor cells which exhibit this splice variant. 11 A recent study by Cao et al found that AR-Vs can cause AR-FL to induce gene expression in the absence of androgen, in addition to AR-V ability to be active in the absence of androgen on their own.…”
mentioning
confidence: 99%
“…11 A recent study by Cao et al found that AR-Vs can cause AR-FL to induce gene expression in the absence of androgen, in addition to AR-V ability to be active in the absence of androgen on their own. 10 Targeting both AR-V7 and the AR-ligand binding domain may help prevent resistance mechanisms from emerging.…”
mentioning
confidence: 99%
See 1 more Smart Citation